SME support for halal industry and sharia economy in Indonesia: SWOT analysis - Azwar, Azwar; Bin Sarip, Mohd Musa (Faculty of Business & Economics, Universitas Islam Indonesia, 2024)
Purpose – This study aims to identify and analyze the strengths, weaknesses, opportunities, and threats as well as strategies related to micro, small, and medium enterprises (SME) support in the development of the halal industry and the Sharia economy in Indonesia.Methodology – This study used a mixed-method approach in the form of a sequential exploratory design with strengths, weaknesses, opportunities, and threats (SWOT) analysis.Findings – This study highlights the vast number of SMEs and their workforce as significant strengths. However, the lack of digital technology integration among SMEs is a weakness. Opportunities include a large Muslim population and availability of institutions willing to provide loans. However, threats emerge from low awareness among Indonesian Muslims regarding halal products. The proposed strategies include enhancing financing facilities, government subsidy programs, awareness campaigns, ecosystem strengthening, and socialization efforts.Implications – The findings offer practical insights for supporting SMEs, including improving access to financing and increasing awareness among Indonesian Muslims. Socially, the study suggests potential benefits such as fostering economic growth, creating employment opportunities, and promoting the production and consumption of halal products. Overall, this study provides valuable guidance for policymakers and stakeholders interested in enhancing SME support in Indonesia's halal industry and Islamic economy, with implications for economic and social development.Originality – The study's original contribution lies in its comprehensive analysis of SMEs in Indonesia within the context of the halal industry and Islamic economy.